Pendistribusian Zakat oleh BAZNAS Kabupaten Pakpak Bharat berdasarkan Undang-Undang Nomor 23 Tahun 2011 tentang Pengelolaan Zakat - Aradimas, M. Ilham; Efendi, Rahmad (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This study aims to examine the implementation of muamalah legal principles in the distribution of zakat by the National Amil Zakat Agency (BAZNAS) of Pakpak Bharat Regency, in accordance with Law No. 23 of 2011. It also seeks to identify the challenges encountered and formulate strategic measures to improve the effectiveness of zakat distribution. The research employs an empirical juridical method, emphasizing primary data obtained directly from BAZNAS Pakpak Bharat through field research. Data were collected through direct observation and interviews with BAZNAS officials, and subsequently analyzed qualitatively to explore the practical application of law within society. The findings indicate that BAZNAS Pakpak Bharat has endeavored to apply the principles of justice, transparency, trustworthiness (amanah), benefit, and legal certainty in zakat distribution. Nevertheless, significant obstacles remain, such as low public awareness of channeling zakat through official institutions, limited human resources, accountability issues, bureaucratic complexity, and the necessity to adapt to socio-economic dynamics. Only 11 out of 78 mosque congregations are registered as Zakat Collection Units (UPZ), reflecting the untapped potential of zakat. Hence, the study recommends strengthening public education, enhancing human resource capacity, improving transparency, developing productive programs, and optimizing the role of UPZ.